Handbook of research on information management and the global landscape - Hunter; Tan 1959- (Advances in global information management, 2009)
"This book related to the many issues surrounding living and working in a global environment, showing how global work being performed with anyone, anywhere, at any time. It relates how necessary it is for companies to conduct business while taking a global perspective to their operations"--Provided by publisher